Spectrum of Grown up Congenital Heart (GUCH) at Armed Forces Institute of Cardiology/ National Institute of Heart Diease: 10 years Experience - Akbar, Hajira; Nawaid, Mohammad Amir; Muzaffar, Tabassum; Imtiaz, Sana; Ansari, Asma (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the spectrum of Grown up Congenital Heart (GUCH) at Armed Forces Institute of Cardiology/National Institute of Heart Dieases. Study Design: Descriptive cross sectional study. Place and Duration of Study: Paediatric Cardiac Surgery and Obstetric department of Armed Force Institute of Cardiology/National Institute of Heart Diease, Rawalpindi Pakistan, from 2011 to 2021. Methodology: It was a descriptive cross sectional study conducted at Paediatric Cardiology, Paediatric Cardiac Surgery and Obstetric department of AFIC/NIHD. After taking informed consent, a total of 1344 patients fulfilling inclusion and exclusion criteria with non probability consecutive sampling were enrolled in study from 2011 to 2021. Diagnosis, transthoracic echocardiography findings, procedural details (cardiac catheterization/cardiac surgery/obstetrical intervention) and outcome of all patients were noted. Results: Out of 1344 patients, 700 patients had cardiac catheterization. Among patients who underwent cardiac cath, 304(43%)were males and 396(56.6%) were females. 279(39%) diagnostic and 421(61%) cardiac interventional procedures were done.Most common procedure done was ASD device closure in 227(32%) patients. Complications were seen in 29(4%) patients and mortality in 3(0.4%) patients. There were a total of 188 patients who underwent congenital cardiac surgery. Out of patients who underwent congenital cardiac surgery procedures, 96(51%) were male and 92(49%) were female patients. Major complications were observed in 51(25%) patients and the mortality was 11(5%).There were total of 456 patients in obstetrics department. Out of 456 patients, 54(11%) were with congenital cardiac lesions .The most common defect was VSD 27(6%)patients and dilated cardiomyopathy (DCM) 27(6%) patients followed by ASD and TOF. The maternal and fetal mortality was12(2.7%) and 22(5.5%) respectively. Conclusion:With immense advancement in diagnosis and management of congenital cardiac diseases, a significant number of patients remain undiagnosed and untreated till the time they present as GUCH. Most common presentation is ASD which is mostly manageable by transcatheter intervention, however late presentation carries a risk of complications like pulmonary hypertension.